2013
DOI: 10.1063/1.4790844
|View full text |Cite
|
Sign up to set email alerts
|

Optically excited multi-band conduction in LaAlO3/SrTiO3 heterostructures

Abstract: The low-temperature resistance of a conducting LaAlO 3 /SrTiO 3 interface with a 10 nm thick LaAlO 3 film decreases by more than 50% after illumination with light of energy higher than the SrTiO 3 band-gap. We explain our observations by optical excitation of an additional high mobility electron channel, which is spatially separated from the photo-excited holes. After illumination, we measure a strongly non-linear Hall resistance which is governed by the concentration and mobility of the photo-excited carriers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 36 publications
(32 reference statements)
8
37
2
Order By: Relevance
“…The observed increase in R PI (at t = 0) with increasing light energy (1.55-3.06 eV) is also in agreement with earlier reports, 13 where finite absorption by in-gap states in STO band gap was responsible for such a behavior. As seen further from Figs.…”
Section: 12supporting
confidence: 81%
See 2 more Smart Citations
“…The observed increase in R PI (at t = 0) with increasing light energy (1.55-3.06 eV) is also in agreement with earlier reports, 13 where finite absorption by in-gap states in STO band gap was responsible for such a behavior. As seen further from Figs.…”
Section: 12supporting
confidence: 81%
“…We need to mention that in Ref. 13, the photo-induced change in the resistance for light energy greater than the STO band-gap has been attributed to a transfer of photoexcited carrier to a subband where the carrier mobility is high; this two-band picture enables Guduru et al 13 to explain the non-linear Hall data. A fiber optic transport probe capable of electrical transport measurements in a range of T = 1.8-300 K, B = 0-7 T (or higher), and light wavelengths between near UV to near IR has been designed, developed, and tested.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar illumination experiments were carried out by Guduru et al at the LAO/STO interface with a LAO layer thickness of 10 nm, as shown in Figure a. Here, they illuminated the interface with different photon energies ranging from 1.44 to 3.65 eV . Upon illumination, the resistance decreased gradually with increasing photon energy, however, with a relatively small decrease observed when the photon energy was smaller than the band gap of STO at approximately 3.4 eV.…”
Section: Light/matter Interactionsupporting
confidence: 68%
“…[1][2][3] Interest is largely focused on the conducting interface between two band-insulating perovskite oxides SrTiO 3 (STO) and LaAlO 3 (LAO), 4 which exhibits properties such as superconductivity, 5 magnetism, [6][7][8][9][10][11] and tunable switching of high mobility interface conductivity. [12][13][14] Although several mechanisms [15][16][17][18] are proposed to be responsible for the interface conductivity, the exact origin and nature of the charge carriers at the interface is still under debate. The major difficulty in achieving consensus about the intrinsic electronic nature of the interfaces is due to the fact that their properties strongly depend on external factors such as the growth conditions of the LAO layer, 6 LAO layer thickness, 19,20 and the configuration of the heterostructures.…”
mentioning
confidence: 99%